Students' Awareness Level On The Dangers Of Drugs - Hikmad Hakim; Sahabuddin Sahabuddin; Muhammad Ishak (Jurnal Olahraga Kebugaran dan Rehabilitasi (JOKER), 2024)
This study aims to determine the level of student knowledge about the dangers of drugs in SMA Negeri 16 Makassar. This research is quantitative and descriptive. The variable in this study is the level of students' knowledge about the dangers of drugs at SMA Negeri 16 Makassar. The population in this study were all students in SMA Negeri 16 Makassar and a sample of 60 people. The data collection technique used is a questionnaire (questionnaire). The data analysis technique used descriptive data analysis techniques with SPSS categorization. The results of this study indicate that the level of knowledge of students about the dangers of drugs at SMA Negeri 16 Makassar for the Narcotics category is in the moderate category as much as 45.0%, for the Psychotropic category in the medium category with a percentage level of 70.0%, and for the Substance category Addictive is in the high category with a percentage of 43.3%. It can be concluded that the level of students' knowledge about the dangers of drugs at SMA Negeri 16 Makassar is in the medium category